Evaluasi Pembelajaran: Efektifitas Pemanfaatan Teknologi sebagai Media Pembelajaran dalam Meningkatkan Keaktifan Siswa di MTS YP3I Muamalah - M. Khaerul Majid H; Abdul Fatah; Suhirman; Akhmad Syahri; Mustain (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The rapid development of technology requires structural adjustments in the world of education, including in Islamic religious institutions. This study aims to determine the effectiveness of utilizing technology, specifically animated video media, in increasing student activity and learning outcomes at MTs YP3I Muamalah. Using a descriptive qualitative approach through field studies and comparative analysis methods, this study evaluates how audio-visual technology can optimize the learning environment. The results showed that the use of audio-visual media, such as animated videos and PowerPoint presentations, was very effective in creating a dynamic classroom atmosphere. This technology visualizes complex concepts into simpler terms, minimizes classroom behavioral disruptions, and significantly increases students' learning motivation, engagement, and vocabulary memorization (mufradat) in Arabic and Islamic Education (PAI) subjects. However, constraints such as limited technological infrastructure and the urgent need for teacher training remain substantial challenges that must be addressed for optimal implementation.